2016
DOI: 10.1590/1517-869220162204159074
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Anterior Cruciate Ligament Reconstruction in Brazil's Public Health System

Abstract: Introduction: Several studies have reported on the epidemiology of Anterior Cruciate Ligament Reconstruction (ACLR) in Europe and North America; however, there is currently no data relating to Brazil. Objective: To describe the incidence of ACLR in Brazil and investigate temporal trends and differences between age and sex groups. Methods: All reported ACLR cases in the public hospital system between January 2008 and December 2014 were extracted from the Information Technology Department of the Brazilian Minist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 23 publications
0
12
0
7
Order By: Relevance
“…The authors also identified a significant increase in total admission costs per case. Lopes et al[ 27 ] evaluated the epidemiology of ACLR in the Brazilian public health system and reported an average length of stay of 1.8 days in 2014. In the same study, the authors showed a reduction in hospital length of stay over several years.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also identified a significant increase in total admission costs per case. Lopes et al[ 27 ] evaluated the epidemiology of ACLR in the Brazilian public health system and reported an average length of stay of 1.8 days in 2014. In the same study, the authors showed a reduction in hospital length of stay over several years.…”
Section: Discussionmentioning
confidence: 99%
“…11 A similar male predominance (M:F, 1.5:1) among Indian such patients has been reported by Gupta et al in 2014. 10 Lopes et al (2016) reported a male to female ratio of 4.6:1 in Brazilian such patients 12 while Abd Razak et al reported it to be 4.9:1 in Singapore. 13 In the present study, the mean BMI of the patients was 27.35±4.24 Kg/m 2 .…”
Section: Discussionmentioning
confidence: 98%
“…The results of this study support the efficacy of the hemostatic capacity of the bi-component to prevent the spread of bleeding as well as increase its residual absorption in the immediate postoperative period. Electrocautery is one of the most common methods of achieving hemostasis (1). However, by performing electrocautery of the tissues, surgeons cause carbonization, that is, we controlled the bleeding by damaging the tissue around it.…”
Section: Discussionmentioning
confidence: 99%
“…Despite being a highly popular graft choice, the comorbidities resulting from the harvest of gracilis and semitendinosus muscle tendons to the anterior cruciate ligament (ACL) reconstruction are a substantial source of patient morbidity and disturb rehabilitation in the early postoperative period (1,2).…”
Section: Introductionmentioning
confidence: 99%